2003
DOI: 10.1111/j.1572-0241.2003.07416.x
|View full text |Cite
|
Sign up to set email alerts
|

Tnf-α− 308A Promoter Polymorphism Is Associated With Enhanced Tnf-α Production and Inflammatory Activity in Crohn's Patients With Fistulizing Disease

Abstract: TNF-alpha -308A polymorphism is associated with enhanced TNF-alpha production, more intense inflammatory activity, and an increased risk for arthritis susceptibility in CD patients with fistulizing disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 33 publications
3
75
0
2
Order By: Relevance
“…These 11 studies contained a combined total of 2000 CD patients and 3499 healthy controls. Sample sizes in the 11 studies varied from 150-846 and publication years were from 1999-2014 (Negoro et al, 1999;González et al, 2003;Balding et al, 2004;Fowler et al, 2005;Song et al, 2005;Zipperlen et al, 2005;Fidder et al, 2006;Yang et al, 2006;Mittal et al, 2007;Hradsky et al, 2008;López-Hernández et al, 2014). Of these, 7 studies were conducted in Caucasians and the other 4 studies were in Asians.…”
Section: Resultsmentioning
confidence: 99%
“…These 11 studies contained a combined total of 2000 CD patients and 3499 healthy controls. Sample sizes in the 11 studies varied from 150-846 and publication years were from 1999-2014 (Negoro et al, 1999;González et al, 2003;Balding et al, 2004;Fowler et al, 2005;Song et al, 2005;Zipperlen et al, 2005;Fidder et al, 2006;Yang et al, 2006;Mittal et al, 2007;Hradsky et al, 2008;López-Hernández et al, 2014). Of these, 7 studies were conducted in Caucasians and the other 4 studies were in Asians.…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological data have shown that up to a quarter of patients became steroiddependent and 20% steroid-resistant within 1 year [28]. Although the mechanism of steroid resistance is unclear, it is known that TNF-α levels are increased in carriers of the uncommon -308A allele [26] and TNF-α was demonstrated to induce dysregulation of the intestinal barrier regulating the tight junctions (TJ) leading to increased permeability. A number of study have suggested that the elevated levels of TNF-α present in CD patients are responsible for the observed increases in intestinal permeability seen in these patients [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA samples were extracted from peripheral blood leukocytes, according to standard protocols [26] and genotyped at the Molecular Laboratory of the Unit of Gastroenterology of the San Giovanni Rotondo Hospital, Italy.…”
Section: Genotypingmentioning
confidence: 99%
“…Furthermore, among the three TNFα promoter haplotypes resolved, AG haplotype was over represented in our CD cohort as compared with control subjects (OR=1,89; CI=1,02; 3,50). According to our data, selected studies of SNPs in the TNF promoter region have been found to be associated with IBD [31][32][33]. A Japanese study reported a significantly increased incidence of polymorphisms in the promoter region of the TNFα at positions -1031, -863, and -857 in patients with CD, versus ethnically matched controls [34,35] in a study on Korean patients observed a significantly higher frequency of -238A allele of TNF-α in CD patients with perianal lesions compared with patients without perianal disease.…”
Section: Discussionmentioning
confidence: 99%